2017
DOI: 10.1039/c7ra07155h
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes of oil fly ash as lubricant additives for different base oils and their tribology performance

Abstract: Oil fly ash has been reported to be a good source for the production of carbon nanotubes (CNTs). Recently, these CNTs were evaluated as lubricant additives in sunflower base oil and were found to exhibit excellent tribological properties. In this work, these CNTs were tested as lubricant additives in 100SN, 500SN and 150BS Saudi Aramco base oils. The results on other commercial carbon nanostructures like multiwall and single wall CNTs and graphene are also included in this study for comparison. Excellent tribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…It was reported that the CNTs of HFOA exhibited superior tribological characteristics at 0.1 wt% compared to the other carbon nanomaterials, and being the best lubricant additives, CNTs of HFOA improved the fuel economy by minimizing friction. [106]…”
Section: Lubricant Additivesmentioning
confidence: 99%
“…It was reported that the CNTs of HFOA exhibited superior tribological characteristics at 0.1 wt% compared to the other carbon nanomaterials, and being the best lubricant additives, CNTs of HFOA improved the fuel economy by minimizing friction. [106]…”
Section: Lubricant Additivesmentioning
confidence: 99%
“…Such CNTs were recently evaluated for some applications, as lubricant additives 1012 and for water treatment 13 . Their performance as lubricant additives was found to be superior to those of other well-known commercially available carbon nanomaterials like multi-walled CNTs, single-walled CNTs, and graphene 11,12 . On the basis of these achievements, it is of great importance to test the CNTs of oil fly ash as a reinforcing material for different polymers.…”
Section: Introductionmentioning
confidence: 98%
“…In the figure, intense peaks are seen at 1340 cm −1 , 1600 cm −1 , and 2700 cm −1 that corresponds to D, G, and 2D graphitic structures. 4953 It is important to mention that the intensity ratio of I 2D /I G increases from 0.18 to 0.37 for the surfactant functionalized formulated oil, which corresponds to the disintegration of graphite and exfoliation of graphitic layers under sliding action. 54 The ratio I G /I 2D decreases as the number of layers decrease.…”
Section: Resultsmentioning
confidence: 99%